Individual and team performance in team-handball: A review - Wagner, H.; Finkenzeller, T.; Würth, S.; von Duvillard, S. P. (Journal of Sports Science & Medicine, 2014)
Team handball is a complex sport game that is determined by the individual performance of each player as well as tactical components and interaction of the team. The aim of this review was to specify the elements of team-handball performance based on scientific studies and practical experience, and to convey perspectives for practical implication. Scientific studies were identified via data bases of PubMed, Web of Knowledge, SPORT Discus, Google Scholar, and Hercules. A total of 56 articles met the inclusion criteria. In addition, we supplemented the review with 13 additional articles, proceedings and book sections. It was found that the specific characteristics of team-handball with frequent intensity changes, team-handball techniques, hard body confrontations, mental skills and social factors specify the determinants of coordination, endurance, strength and cognition. Although we found comprehensive studies examining individual performance in team-handball players of different experience level, sex or age, there is a lack of studies, particularly for team-handball specific training, as well as cognition and social factors.